Artificial seed production from encapsulated micro shoots of Saintpaulia ionantha Wendl. (African Violet) - Daud, N.; Taha, R.M.; Hasbullah, N.A. (2008)
Artificial seeds were produced from encapsulated micro shoots of Saintpaulia ionantha Wendl. (African violet). The production of artificial seeds of this species gave ideal beads based on firmness, texture, size and shape of beads. The percentage of germination from encapsulated micro shoots influenced by the concentrations of sodium alginate and calcium chloride (CaCl2.2H2O) used. It was found that among the concentrations tested, 3 sodium alginate and the exposure to 1.00 mM CaCl2.2H2O solution for 30 min had produced optimal beads with firm, clear, round and uniform size and suitable for handling. It was also observed that micro shoots obtained from optimization of encapsulation matrix showed the highest percentage of germination (84). Encapsulated micro shoots exposed for 30 min in 100 mM CaCl2.2H2O solution gave the optimal time of hardening process. The findings suggested that the encapsulation method for micro shoots could be used as an alternative to artificial seed derived from somatic embryos of Saintpaulia ionantha. Â© 2008 Asian Network for Scientific Information.